Dudley Wright Knox papers - Knox, Dudley Wright, 1877-1960.; Knox, Dudley Wright, 1877-1960.
Correspondence, subject files, speeches, articles, book file, printed matter, newspaper clippings, and other material relating to Knox's activities as director of the U.S. Office of Naval Records and Library (1921-1946), as secretary of the Naval Historical Foundation (1926-1946), and as an author of books and articles on naval affairs. The papers document Knox's views on international naval limitation conferences, naval aviation, the revival of a strong merchant marine, naval readiness, relations with East Asia, foreign trade, and national defense. Includes typescripts and letters, reviews, and clippings relating to Knox's book, A History of the United States Navy (1936). Also includes photocopies of correspondence, memoranda, and other documents pertaining to efforts by Knox and President Franklin D. Roosevelt to publish naval records concerning American wars.
Chief correspondent is Thomas Goddard Frothingham. Other correspondents include J. H. Adams, John V. Babcock, Earle Henry Balch, Harry Alexander Baldridge, Hanson Weightman Baldwin, James Phinney Baxter, Charles Bittinger, Wilson Brown, Howard G. Brownson, Willard H. Brownson, Raymond Leslie Buell, Charles Perry Burt, Kenneth G. Castleman, Bennett Cerf, William Bell Clark, Wat Tyler Cluverius, George P. Colvocoresses, Albert Lyman Cox, Leonard M. Cox, Thomas T. Craven, Josephus Daniels, Ralph E. Davis, Harvey A. DeWeerd, Philip Robert Dillon, Ralph Earle, Edwin A. Falk, Guy Stanton Ford, George Edmund Foss, Julius Augustus Furer, William Howard Gardiner, Charles E. Gilpin, Harpur Allen Gosnell, Edwin E. Grabhorn, Fitzhugh Green, Kent Roberts Greenfield, F. Griffith, John George Hartwig, Jan Hasbrouck, N. A. Helmer, Roy Hoffman, James J. Hogan, Franklin Henry Hooper, Alfred G. Howe, Hiram Johnson, Ira Rich Kent, John Knox, Warren B. Koehler, William Chauncey Langdon, Robert J. LaPorte, Henry Cabot Lodge, Stanford E. Moses, Orson D. Mumm, R. E. Pope, Charles N. Robinson, William Sowden Simms, Edward E. Spafford, J. D. Springer, Harold R. Stark, and Lewis L. Strauss.
Naval officer and historian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Adams, J. H. -- 1871-1927 -- Correspondence; Babcock, John V. -- Correspondence; Balch, Earle Henry, -- 1893- -- Correspondence; Baldridge, Harry Alexander, -- 1880-1952 -- Correspondence; Baldwin, Hanson Weightman, -- 1903-1991 -- Correspondence; Baxter, James Phinney, -- 1893-1975 -- Correspondence; Bittinger, Charles, -- 1879-1970 -- Correspondence; Brown, Wilson, -- 1882-1957 -- Correspondence; Brownson, Howard G. -- 1886- -- Correspondence; Brownson, Willard H. -- 1845-1935 -- Correspondence; Buell, Raymond Leslie, -- 1896-1946 -- Correspondence; Burt, Charles Perry, -- 1876-1949 -- Correspondence; Castleman, Kenneth G. -- 1876-1954 -- Correspondence; Cerf, Bennett, -- 1898-1971 -- Correspondence; Clark, William Bell, -- 1889-1968 -- Correspondence; Cluverius, Wat Tyler -- Correspondence; Colvocoresses, George P. -- 1847-1932 -- Correspondence; Cox, Albert Lyman, -- 1883-1965 -- Correspondence; Cox, Leonard M. -- 1870-1943 -- Correspondence; Craven, Thomas T. -- 1873-1950 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Davis, Ralph E. -- Correspondence; DeWeerd, Harvey A. -- 1902-1979 -- Correspondence; Dillon, Philip Robert, -- 1868- -- Correspondence; Earle, Ralph, -- 1874-1939 -- Correspondence; Falk, Edwin A. -- 1894- -- Correspondence; Ford, Guy Stanton, -- 1873-1962 -- Correspondence; Foss, George Edmund, -- 1863-1936 -- Correspondence; Frothingham, Thomas Goddard, -- 1865-1937 -- Correspondence; Furer, Julius Augustus, -- 1880-1963 -- Correspondence; Gardiner, William Howard, -- 1875-1952 -- Correspondence; Gosnell, Harpur Allen, -- 1890- -- Correspondence; Grabhorn, Edwin E. -- Correspondence; Green, Fitzhugh, -- 1888-1947 -- Correspondence; Greenfield, Kent Roberts, -- 1893-1967 -- Correspondence; Griffith, F. -- Correspondence; Hartwig, John George -- Correspondence; Hasbrouck, Jan -- Correspondence; Helmer, N. A. -- Correspondence; Hoffman, Roy, -- 1869- -- Correspondence; Hogan, James J. -- Correspondence; Hooper, Franklin Henry, -- 1862-1940 -- Correspondence; Howe, Alfred G. -- 1878-1970 -- Correspondence; Johnson, Hiram, -- 1866-1945 -- Correspondence; Kent, Ira Rich, -- 1876-1945 -- Correspondence; Knox, John Crawford -- Correspondence; Koehler, Warren B. -- Correspondence; Langdon, William Chauncy, -- 1871-1947 -- Correspondence; LaPorte, Robert J. S. -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Moses, Stanford E. -- 1872-1950 -- Correspondence; Mumm, Orson D. -- Correspondence; Pope, R. E. -- 1875-1959 -- Correspondence; Robinson, Charles N. -- 1849-1936 -- Correspondence; Roosevelt, Franklin D. -- 1914-1988 -- Correspondence; Sims, William Sowden, -- 1858-1936 -- Correspondence; Spafford, Edward E. -- 1878-1941 -- Correspondence; Springer, J. D. -- Correspondence; Stark, Harold R. -- 1880-1972 -- Correspondence; Strauss, Lewis L. -- Correspondence